Heart transplantation for dilated cardiomyopathy. Issue 5 (November 1995) - Adwani, S S; Whitehead, B F; Rees, P G; Whitmore, P; Fabre, J W; Elliott, M J; de Leval, M R
Abstract : Between 1988 and 1994, 23 patients underwent heart transplantation for dilated cardiomyopathy. The age of the 13 boys and 10 girls was from 8 months to 16 years (mean 7.1 years). Selection criteria included failure to thrive despite maximal antifailure treatment and/or intravenous inotrope dependence. The aetiology of cardiomyopathy was idiopathic (n = 13), congenital (n = 3), anthracycline induced (n = 4), Barth's syndrome (n = 1), and maternal systemic lupus erythematosus (n = 2). The waiting period of heart transplantation ranged from one day to 147 days (mean 22 days). Maintenance immunosuppression included cyclosporin, azathioprine, and prednisolone. Follow up after transplantation was from one month to 62 months (median 27 months) with a mean actuarial survival of 95% at one year and 87% at three years. Four patients developed coronary artery disease, one of whom died as a consequence 15 months after heart transplantation. Heart transplantation has emerged as an acceptable therapeutic option, at least in the short term, for patients with dilated cardiomyopathy.